Aplicación del Enfoque de la Administración por Objetivos para la Implementación de la Norma ISO 9000 para Potencializar la Comercialización de Seguros de Vida en la empresa EQUIVIDA S.A. - Espín Toala, Wendy Johanna (2011)
To determine the viable market that supports this project was necessary to segment potential consumers to determine the target market segmentation variables were geographic, demographic and psychographic; the result could establish a number of surveys needed to draw inferences from mercadológico character. In the 384 surveys it was determined that 73% believe that the purchase of life insurance as an investment and not an expense, which determines that there is a potential market that supports the project.